2022
DOI: 10.3390/microorganisms10122310
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Biochar and Bioorganic Fertilizer on Rhizosphere Bacteria in Saline–Alkali Soil

Abstract: Biochar and bioorganic fertilizers (BOF) that are used in agriculture can, both directly and indirectly, impact rhizosphere soil microorganisms. However, changes to the halophyte rhizosphere bacterial community after applying biochar and BOF to saline–alkali soil have not been thoroughly described. This study has investigated the bacterial communities of halophytes in saline–alkali soil through the addition of different biochar and BOF formulas using Illumina-based sequencing of the 16S rRNA gene fragment. B_B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Although many researches have explored the effects of biochar and organic fertilizer in agricultural fields, only a few have conducted saline–alkali field experiments ( Yao et al, 2017 ; Gu et al, 2022a , 2022b , 2023 ). Biochar amendment and application of organic fertilizer generally changes soil quality, such as pH, soil organic carbon, and nutrient content ( Lehmann et al, 2011 ; Luo et al, 2014 ; Yao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many researches have explored the effects of biochar and organic fertilizer in agricultural fields, only a few have conducted saline–alkali field experiments ( Yao et al, 2017 ; Gu et al, 2022a , 2022b , 2023 ). Biochar amendment and application of organic fertilizer generally changes soil quality, such as pH, soil organic carbon, and nutrient content ( Lehmann et al, 2011 ; Luo et al, 2014 ; Yao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other field management followed local management practice. At the end of the field trial, wheat rhizosphere soil was obtained from the tilled area (0–20 cm) and collected and processed according to Gu et al (2022a) . Then, the collected samples were split into two parts: one for high-throughput sequencing, the other for soil physicochemical properties after being air-dried to remove impurities.…”
Section: Methodsmentioning
confidence: 99%
“…The results indicated that biochar increased soil organic matter, nitrate nitrogen, and quick‐acting phosphorus, thereby improving the physicochemical and biological properties of the saline‐alkali soils and promoting crop growth. In Gu et al (2022) study, the synergistic use of biochar and bioorganic fertilizer proved beneficial. It led to improved soil physicochemical properties, increased inter‐root bacterial diversity, and positively influenced plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Zhang et al (2022) revealed that long-term organic fertilizer application facilitates the proliferation of plant growth-promoting bacteria groups, such as Thiobacillus, Methylobacter, Rhodoferax, Lysobacter, and Flavobacterium, while the abundance of the halophilic genera was significantly decreased. Soil ameliorants, consisting of beneficial functional microbes (PGPR) along with a suitable substrate, are a specialized type of fertilizer that not only improve the soil physicochemical properties and enhance nutrient supply capacity but also alter the soil microbial community ( Lu et al, 2020 ; Gu et al, 2022 ; Huang J. et al, 2023 ). Numerous studies have provided evidence that soil ameliorant application can serve as an effective strategy for improving soil properties ( Naher et al, 2021 ), promoting soil microbial activities that are closely associated with nutrient cycling and disease resistance ( Lu et al, 2020 ; Huang B. et al, 2023 ), and enhancing soil fertility in a saline–alkali ecosystem ( Chen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%